Violencia intrafamiliar y su incidencia en la adaptación escolar de los niños de sexto y séptimo año de educación general básica de la Escuela Ciudad de Zaruma del Cantón Zaruma en el periódo lectivo 2012-2013. - Asanza Feijoó, Gina Maribel (2012)
Domestic violence is one that takes place within the family, whether the aggressor behaves or has shared the same residence, and comprising, among others, rape, physical abuse, psychological and sexual abuse.